2014
DOI: 10.1158/0008-5472.can-14-1151
|View full text |Cite
|
Sign up to set email alerts
|

TLR9 Is Critical for Glioma Stem Cell Maintenance and Targeting

Abstract: Understanding supports for cancer stem-like cells in malignant glioma may suggest therapeutic strategies for their elimination. Here we show that the Toll-like receptor TLR9 is elevated in glioma stem-like cells (GSC) where it contributes to glioma growth. TLR9 overexpression is regulated by STAT3 which was required for GSC maintenance. Stimulation of TLR9 with a CpG ligand (CpG ODN) promoted GSC growth, whereas silencing TLR9 expression abrogated GSC development. CpG-ODN treatment induced Frizzled4-dependent … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 49 publications
(78 reference statements)
2
62
0
Order By: Relevance
“…Importantly, the percentage of CD5 + B cells was significantly expanded in tumors (Figure 1A). STAT3 is a transcription factor known to upregulate expression of several of its own upstream activators (Herrmann et al, 2014; Kortylewski et al, 2009; Lee et al, 2010; Xin et al, 2013; Yu et al, 2009). We therefore explored the possibility that STAT3 upregulates CD5 expression, thereby forming a feed-forward loop in B cells to promote tumor progression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, the percentage of CD5 + B cells was significantly expanded in tumors (Figure 1A). STAT3 is a transcription factor known to upregulate expression of several of its own upstream activators (Herrmann et al, 2014; Kortylewski et al, 2009; Lee et al, 2010; Xin et al, 2013; Yu et al, 2009). We therefore explored the possibility that STAT3 upregulates CD5 expression, thereby forming a feed-forward loop in B cells to promote tumor progression.…”
Section: Resultsmentioning
confidence: 99%
“…Activation of STAT3 in tumor cells and in the tumor microenvironment is contributed by many factors, albeit a critical role of IL-6 (Kujawski et al, 2008; Wang et al, 2009). In addition to multiple cytokines and growth factors, chemokines and other ligands of GPCRs including sphingosine-1-phosphate (S1P), have been shown to be critical for persistent activation of STAT3 in tumor, including many types of immune cells in the tumor microenvironment (Deng et al, 2012; Herrmann et al, 2014; Lee et al, 2010; Lee et al, 2009). A common feature of STAT3 activation is that STAT3 regulates expression of their receptors, which in turn activate STAT3, even in the absence of abundant amounts of their ligands.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, high contents of stromal inflammation, CAFs and MICs overexpressing TLR9 and numerous cytotoxic CD8 lymphocytes were also associated with a better prognosis [43]. Cancer-associated chronic inflammation initiated by epithelial cancer cells and stromal/immune cells overexpressing TLR9, is amplified and sustained by a chemokine inducer composed of activated NF-kB and STAT3 [44,45] which may promote cancer progression and therapeutic resistance [46]. Furthermore, several studies identified TLRs, such as TLR9, as crucial activators of the JAK-STAT3 pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several studies identified TLRs, such as TLR9, as crucial activators of the JAK-STAT3 pathway. Recent data showed that TLR9 is highly expressed in glioblastoma stem-like cells (GSCs) [46] and that activated STAT3 binds to the TLR9 promoter and contributes to TLR9 expression in GSCs [47], providing a potential mechanism by which infection or inflammation enhances carcinogenesis. In our series of 80 TNCs, we observed that in TNCs with TLR9 overexpression, nuclear phosphoSTAT3 (Tyr705) was identified in 81 % of cancer cells as compared to 31 % of cancer cells in TNCs with normal or low TLR9 level of expression.…”
Section: Discussionmentioning
confidence: 99%
“…[12, 35] TLR9 is also commonly elevated in cancer cells in many hematologic malignancies, including acute myeloid leukemia (AML), multiple myeloma and B cell lymphoma as well as in certain solid tumors, such as prostate cancers or malignant glioma. [23, 36–38] The efficacy of CpG-conjugates is determined not only by TLR9, as TLR9 partners with SRs on the cell surface for conjugate uptake. Noteworthy, SRs expression has been reported in hematologic malignancies and also in various solid tumors, e.g.…”
Section: It Takes Two To Deliver: Tlr9 and Scavenger Receptorsmentioning
confidence: 99%